Pesticides & alternatives - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Pesticides & alternatives Pesticide Action Network Africa Regional Center, BP 15938 Dakar-Fann, Dakar, SENEGAL